Geographical Spread of Global Emissions: Within-country Inequalities Are Increasing - Caspar Sauter; Jean-Marie Grether; Nicole A. Mathys (University of Neuchâtel, Institute of Economic Research (IRENE), 2015)
The major greenhouse gases, CO2 and CH4, are uniformly mixing, but spatial inequalities in emissions do matter in terms of both efficiency and equity of environmental policy formation and implementation. As the recent evidence has mainly focused on convergence issues between countries, this paper extends the empirical analysis by taking into account within-country inequalities in emissions of three major atmospheric pollutants: CO2, SO2 and CH4 over the 1970-2008 period. Using Theil-index decompositions, we show that within-country inequalities account for the bulk of global inequality, and tend to increase over the sample period, in contrast with diminishing between-country inequalities. An original extension to include differences across sectors reveals that between-sector inequality matters more than between-country inequality, and becomes the dominant source of global inequality at the end of the sample period in the CO2 and SO2 cases. A final exercise suggests that social tensions arising from the disconnection between emissions and future damages are easing for CO2 but rather stable for CH4. These orders of magnitude should be kept in mind while discussing the efficiency and fairness of alternative paths in combating global warming.
Keywords: O13; D63; Q53; Q54; Q58; 330; Global spatial emission inequality; sub-national emission inequality; CO2; SO2; CH4